Oxidation of Iron - Goursat, Albert Gilbert (My University, 1972)
The main objective of this study was to gain an understanding of the oxidation properties of iron at low oxygen pressures and at high temperature.
A thermogravimetric technique was employed to investigate the oxidation of iron in oxygen over the pressure range 2.5×10⁻³ - 3.0×10⁻¹ torr at temperatures ranging between 750ºC and 1000ºC. The oxidation curves exhibited distinct intervals of linear kinetics followed by transition to intervals of parabolic kinetics during exposures extending to 125 min. Linear kinetics governing the growth of uniformly thick wustite scales; the linear rate constants showed a proportional dependence on oxygen pressure due to reaction control by a phase boundary reaction involving non-dissociation adsorption of oxygen. Parabolic kinetics governed growth of wustite-magnetite scales containing magnetite as outermost layers. The value of the parabolic rate constants were independent of oxygen pressure since scale growth was directly dependent on the iron vacancy gradient in wustite established by the oxygen activities at the Fe/FeO and FeO/Fe₃O₄ interfaces.
Scanning electron microscopy techniques were used to gain information on the growth of magnetite and hematite layers in the multilayer scale consisting largely of wustite formed at high temperature in the pressure range 2.5×10⁻³ to 760 torr.
Keywords: materials science; iron; Fe; oxidation; thermogravimetric; kinetics